PENGUJIAN HIPOTESIS DALAM PENELITIAN KUANTITATIF: SEBUAH REVIEW KRITIS ATAS PRAKTIK, PROBLEMATIKA, DAN ALTERNATIF DALAM PENDIDIKAN DASAR - Hulpiana; Rias Sandi Miswardani; Dina Irilianti; Edi Waluyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Hypothesis testing is a fundamental pillar of quantitative research in the field of basic education, but its practice over the past few decades has faced profound epistemological criticism. This article presents a critical review of the literature on hypothesis testing in quantitative research in primary education, with a focus on the identification of research gaps, criticism of Null Hypothesis Significance Testing (NHST), and the synthesis of alternative frameworks. Using the Critical Interpretive Synthesis (CIS) method enriched by the PRISMA approach for literature selection, this article analyzes 83 selected studies from the period 2000–2026. The findings show that (1) NHST practices dominate primary education research with a misinterpretation rate of non-significant outcomes reaching 56%; (2) there is a systematic gap between the statistical practices taught and those practiced in the research; (3) alternatives such as effect size, confidence interval, equivalence testing, and Bayesian approaches are still limited in their use; (4) Questionable research practices such as P-hacking have been empirically identified in the educational literature. This article offers an alternative conceptual framework that integrates estimation thinking with the pedagogical context of basic education, as well as recommends reforms in training research methodologies and publication practices